MSU MEDICAL COLLEGES BLENDED LEARNING FOR FIRST YEAR SCIENCE COURSES: UNITING PEDAGOGY TO MAXIMIZE EXPERIENCE AND REAL WORLD LIMITATIONS - Lovell, Kathryn (Online Learning, 2009)
At Michigan State University the two medical schools, College of Human Medicine (CHM; M.D. degree) and College of Osteopathic Medicine (COM; D.O. degree), have offered the same science courses to first year students for many years. Science departments report to both colleges, and the same faculty can effectively teach the content required in the first year of medical school. The faculty have created online resources to maximize student choice and learning approaches. For example, classroom lectures (audio and screen video) are recorded; online homework may contribute to the course grade; virtual microscope software and material for histology laboratory is available online in addition to computer-based laboratory sessions with instructors present; and many practice exams are available online. MSU is expanding to three new campuses during the 2008–2010 period. CHM will open a sister campus in Grand Rapids, while COM will open two branch campuses in southeast Michigan. The goal is to make the learning experiences equivalent for all students at all campuses. Faculty, staff and administrators have met on a regular basis to discuss working toward a NSF CyberInfrastructure model where all basic science learning experiences (with the exception of gross anatomy lab) are available online. These online resources will be coupled with face to face learning as well. Currently, efforts to make course materials available online in the most effective manner are underway. Discussion about how to provide online communication channels is also progressing. Numerous debates have occurred on how best to facilitate student learning in multiple locations using new technology tools, recognizing the goal for students is not only to pass medical board exams but also to acquire life-long learning skills in an ever changing medical and science environment. The authors will share not only processes used, but also perspectives on best approaches and strategies to determine what students find effective.